An updated meta-analysis of the primed goal-organizational behaviour relationship. Issue 4 (12th April 2023) - Latham, Gary P.; Chen, Xiao; Piccolo, Ronald F.; Itzchakov, Guy
Abstract : Environmental cues (e.g. achievement-related words and pictures) can prime/activate, in the absence of awareness, a mental representation of importance stored in memory. Chen et al .'s 2021 Applied Psychology: An International Review 70, 216–253. (doi:10.1111/apps.12239 ) meta-analysis revealed a moderate, significant overall effect for the goal priming-organizational behaviour relationship, with three moderators identified: context-specific versus a general prime, prime modality (i.e. visual versus linguistic) and experimental setting (field versus laboratory). An independent researcher found that their finding was negligibly affected by a publication bias. Shanks & Vadillo (2021), Royal Society Open Science 8, 210544. (doi:10.1098/rsos.210544 ) (field: k = 13, N = 683, d = 0.64), questioned Chen et al .'s conclusion regarding the effect size found in field studies (field: k = 8, N = 357, d = 0.68). In this paper, we discussed Shanks & Vadillo's selection of additional field experiments that led to their conclusion of a publication bias. We updated Chen et al .'s meta-analysis to include relevant studies conducted since that study's publication. The present meta-analysis reproduced the original findings in Chen et al . (field: k = 11, N = 534, d = 0.67). The updated findings are consistent with: (i) laboratory findings, (ii) the findings obtained in field experiments on consciously set goals and (iii) goal setting theory (Latham & Locke, 2018 In Handbook of industrial, work & organizational Psychology, vol. 1 (eds D Ones, N Anderson, C Viswesvaran, H Sinangil), pp. 103–124).